Subprime mortgage default rates, spread volatility and contagion to stock markets. - Choo, Choi Harn. (2008)
This thesis studies (i) the impact of the subprime mortgage crisis on the mortgage-backed CDS market and equity markets using the ABX.HE indices and the S&P 500 and DJIA Index, (ii) the underlying parameters such as implied spreads, default probabilities and long-term implications of the subprime mortgage crisis.